Possibility of Application of Topological Consideration for Grain Boundaries in Nanosilicon Films - N.G. Nakhodkin; T.V. Rodionova (Журнал нано- та електронної фізики)
A comparative analysis of the experimentally observed by atomic force microscopy grain boundary structure of nanosilicon films with the existing model representations was carried out. It is shown that the topological model of structural changes may be used for the analysis of changes of grain boundary structure only for films with equiaxial structure. For films with fibrous structure topological model is unacceptable because of the large number of multiple joints grain boundaries and grain boundaries faceting.